An investigation of an arc furnace load in the 1973 Luzon Grid - Ramas, Jose T. (1971)
This study deals with an actual problem is the local electric power industry, although the treatment is made general so that it may serve as basis for similar investigations later. In this study, a proposed Billet Manufacturing Plant, designed to use two 25-ton electric arc furnaces, is proposed to be connected to the 1973 Luzon Grid by National Power Corporation. The use and operation of electric arc furnaces are usually associated with voltage flicker problems introduced to the electric power supply system. Hence, NPC is concerned with the possible adverse effects ehich this arc furnace load may introduce to the 1973 Luzon Grid. There are at present no specific rules to follow to ensure that the operation of new arc furnace installations will not introduce undesirable effects to the electric power supply system. The common practice to date appears to be that each new arc furnace installation practice an overall investigation which includes the power supply system. Thus, this investigation was pursued and in the process adopted the methods of solutions used in the AIEE Committee Reports CP 55-802(1) and Paper 57-56 (3). This study made use also of the Load Flow and Fault Programs of the UP-IRC Power System Computer Service. Initial findings show that the arc furnace load will not introduce objectionable voltage fluctuations nor voltage flicker at any of the existing loads in the 1973 Luzon Grid. However, the two immediate buses to the steel plant will experience objectionable voltage flicker. Thus, the study proposed suitable measures to reduce the undesirable effects to acceptable level at these two immediate buses to which new loads may be connected in the future. These measures proposed the use of buffer reactors and a synchronous condenser as compensating equipment. Furthermore, the optimum ratings of the buffer reactor and synchronous condenser were determined correspondingly. The final results and findings show that the use of the compensating equipment greatly improved the voltage conditions at all the buses in the Luzon Grid. Therefore, it is concluded that connection of the proposed two 25-ton arc furnaces to the 1973 Luzon Grid will not adversely affect the existing loads. However, it is necessary to connect the recommended compensating equipment to ensure that no adverse effects maybe experienced by future loads which maybe connected to the two immediate buses to the steel plant.
Thesis (M. S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric furnaces